Ecofriendly approach for the control of a common insect pest in the food industry, combining polymeric nanoparticles and post-application temperatures - Jesser, Emiliano Nicolás (2020)
One of the most common insect pests is Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), which affects different food commodities. A new effective approach for the management of insect pests is the development of new formulations based on EO However,few works informed about the relationship between insecticidal activity of EO or EOPN and post application temperature. In our work, palmarosa (Cymbopogon martinii (Roxb.) Watson), geranium (Geranium maculatum L.), and peppermint (Mentha piperita L.) oils were formulated in PEG 6000 matrix in order to obtain EOPN Geranium and palmarosa EOPN had sizes of 259 nm and 191 nm, respectively; the encapsulation efficiency (EE) was close to 90% and the samples were monodisperses. The sizes from peppermint EOPN were around 380 nm, EE of 72% and were polidisperse. In contact toxicity bioassay, the insecticidal effect of the oils were increased by all EOPN with palmarosa oil being the most toxic. In addition, the oils and their nanoparticles showed a significant negative temperature coefficient when applied by contact. In fumigant bioassay, just palmarosa and peppermint EOPN enhanced the oil activity, and palmarosa EO and EOPN showed the highest toxic effect. In this case, the EO and EOPN insecticidal activity was unaffected by environmental temperature variation.